Mediation as a means to resolve administrative disputes: an appraisal of the historical and legal aspects. - Rostovska, Karyna Valeriivna; Hryshyna, Nataliia Viktorivna; Kaidash, Olesia Yuryevna; Syromiatnikova, Marharyta Sergeevna (DIXI, 2021)
Purpose: The purpose of the article is a scientific analysis regarding the understanding of the essence and content of mediation as one of the most effective means to resolve administrative and legal disputes, as well as the latest draft laws developed by the Government of Ukraine concerning the regulation of the mediation procedure. These are analyzed, resulting in comments and recommendations aimed at improving their provisions. The methodological basis of this article consists of the methods of scientific cognition commonly used in contemporary legal science, namely: formal-legal, analytical, and structural-functional approaches. The historical and legal aspects of the development of the institution of mediation are also examined. Based on scientific sources, the essence of mediation is clarified and the mediation procedure is analyzed as one of the most promising tools for resolving administrative disputes. The impact of mediation on the quality of resolving administrative and legal conflicts that arise between subjects of administrative-legal relations is also identified. The main principles of the mediation procedure are defined and characterized, particularly voluntariness, confidentiality, sincerity of the parties, and neutrality. Proposals are presented to strengthen the use of modern mediation tools in the resolution of administrative disputes. Emphasis is placed on the successful experience of several developed countries and the possibilities for applying such practices in Ukraine. The authors conclude that resolving administrative disputes through mediation is a highly effective method for conflict resolution. One of its key advantages lies in its voluntary and informal nature, which provides broad opportunities for negotiation to the disputing parties.